Africa-Europe relationship : a multistakeholder perspective - Marchetti, Raffaele (London ; New York : Routledge/Taylor & Francis Group, 2020)
"The relationship between Africa and Europe is of high strategic importance. This volume studies the ongoing dynamics between the two continents by adopting a pluralist understanding of international relations which encompasses non-state actors as well as states. Going beyond pure intergovernmentalism, this focus of this book is on activists, business people, religious believers, local politicians as well as transnational networks and by hybrid coalitions. Such plurality of socio-economic and political interactions underpinning the relationship between Africa and Europe is underexamined and yet of great importance. The text identifies new patterns of cooperation and recurrent obstacles in the African-European multi-stakeholder dynamics, thus opening the way for a more accurate understanding of the future relationship between Africa and Europe. This book brings African and European reflections together, on an equal standing, in order to achieve a true dialogue among civilizations. This book is aimed at all those who are interested in the African-European relationship, including students and researchers, as well as activists, business people, civil servant and functionaries at local and national level"--
Introduction -- A more encompassing understanding of the Africa-European relationship / Raffaele Marchetti -- Civil society organizations -- European-South African elite collaboration, balanced by civil society solidarity / Patrick Bond -- Mission, Development and 'Reverse Mission' in Europe-Africa Religious Relations / Dena Freeman -- The Role of Think Tanks between Africa and the EU / Silvia Menegazzi -- The Exacerbation of Community Confinement: Involved Social Forces and Effects on the Euro-African State Relationship / Belkacem Iratni -- Business organizations -- Bi-continental Encounters for Fairer ACP-EU trade? Assessing Multi-Stakeholder Initiatives / Mark Langan -- Sleeping Beauty Awakens. Africa rise and the new deal with international energy stakeholders / Lapo Pistelli -- The evolution (2000-2017) and proposed future scenarios of EU Africa Relations in Technological innovation: A multi-stakeholder perspective / Robert Mudida -- Institutions -- Eurafrica reconsidered: Europe and African leaders in historical perspectives / Véroniqueque Dimier and Giuliana Gliottone -- Integration Dynamics between the African Union (AU) and the Regional Economic Communities (RECs) in light of a newly oriented Euro-African Geopolitics / Marco Massoni -- Entangled regions: how multiple interregionalisms reshape Central Africa / Frank Mattheis -- Cities in the Africa-Europe Interaction / Elena De Nictolis.
OCLC-licensed vendor bibliographic record.
Keywords: Africa -- Relations -- Europe; Europe -- Relations -- Africa; POLITICAL SCIENCE / General